Response of fennel (Foeniculum vulgare) to inorganic nitrogen, farmyard manure and Azospirillum - JAIN, N K; JAT, N L; CHOUDHARY, G R (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during winter (rabi) seasons from 2000-01 to 2003-04 to study the response of fennel (Foeniculum vulgare Mill.) to inorganic nitrogen, farmyard manure and Azospirillum at Jobner (Rajasthan). Maximum plant height, number of umbelsiplant, seedslumbel and test weight of seed were recorded with the application of inorganic nitrogen (100 %) + Azospirillum @ 1.5 kgka + 5 tonnes farmyard manureha over rest of the treatments. Maximum number of branchestplant and umbelletsiumbel were recordedunder the application of 100 %nitrogen through inorganic source alone and was comparable to inorganic nitrogen (100 %) + Azospirillum @ 1.5 kgha + 5 tonnes farmyard manureha and Azospirillum @ 1.5 kgha + 10 tonnes farmyardmanureiha. The highest seed yield (l 158 kg1 ha), net returns (Rs 22 728 /ha) and benefit: cost ratio (2.28 : 1) were recorded in the treatment of inorganic nitrogen (100 %) + Azospirillllnz @ 1.5 kgha + 5 tonnes farmyard manure/ha.